Kolaborasi Pemerintah, Polisi dan Masyarakat: Pengalaman COP Malioboro - Anggoro, Yanuar Agung (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2006)
Community Oriented Policing (COP) is an effort of monitoring security by stressing on local initiatives, public and private partnership and policing and policing with the community. It is aimed at, establishing and sustaining community-police-government partnership through a problem solving approach responsive to the needs and demands of the community. COP promotes and support organizational strategies to address the causes and to reduce the fear of crime and social disorder. By partnership, COP insist role and paradigm changes of government, police, and community. This paper describe the collaborative effort and their problems among community, police and the local government.